2011
DOI: 10.1002/ijc.26028
|View full text |Cite
|
Sign up to set email alerts
|

The impact of amyloid precursor protein signalling and histone deacetylase inhibition on neprilysin expression in human prostate cells

Abstract: The zinc metallopeptidase, neprilysin (NEP), is an endothelin-1 degrading enzyme whose expression is extensively downregulated in prostate cancer. The expression of NEP in neuronal cells is regulated by intramembrane proteolysis of the amyloid precursor protein (APP) through its intracellular domain (AICD) facilitating histone acetylation of the NEP promoter and gene transcription. The present study has examined whether similar mechanisms operate in prostate cell lines. The expression of APP and its processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…Further, we found treatment of 5-aza-CdR, the wellknown cytosine methylation inhibitor (29), resulted in remarkable increases of NEP expression in N2a/wt and N2a/ APPswe cells, which is consistent with the upregulation of NEP induced by 5-aza-CdR in other age-associated diseases such as prostate cancer (16,35). These data indicate that Fig.…”
Section: Inhibition Of Akt/nf-κb Signaling By Cur Is Associated With supporting
confidence: 80%
“…Further, we found treatment of 5-aza-CdR, the wellknown cytosine methylation inhibitor (29), resulted in remarkable increases of NEP expression in N2a/wt and N2a/ APPswe cells, which is consistent with the upregulation of NEP induced by 5-aza-CdR in other age-associated diseases such as prostate cancer (16,35). These data indicate that Fig.…”
Section: Inhibition Of Akt/nf-κb Signaling By Cur Is Associated With supporting
confidence: 80%
“…It has been however established that nuclear location of AICD and consequent transcriptional regulation is dependent on APP processing through the amyloidogenic pathway [25,26,27]. Although regulation of gene transcription by AICD has been a matter of debate [28,29], probably reflecting the cell specificity of AICD regulation [30,31,32], it has been demonstrated by chromatin immunoprecipitation studies that AICD does interact with promoter regions of putatively regulated genes [24,25]. Here, we have demonstrated that the cleavage of APP by the γ-secretase activity to release AICD is not necessary for APP-mediated regulation of EGR-1 expression, and that AICD does not interact with the EGR-1 promoter in chromatin immunoprecipitation studies.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, it has been recently reported that differentiated PC12 cells, treated with the γ-secretase inhibitor DAPT, show an increase in ganglioside level in neuritic terminals [62], further strengthening that PS proteolytic activity alters ganglioside homeostasis. Additionally, we and others recently found that cleavage products of APP are involved in the regulation of several proteins and that this regulation is disturbed in absence of PS, in mutated PS or in AD [11,30,31,32,63,64,65]. Main focus was attended to the APP intracellular domain (AICD), which is released to the cytosol and discussed to be involved in gene transcription.…”
Section: Discussionmentioning
confidence: 99%